OPTIMALISASI KUALITAS PRODUK DAN LAYANAN UNTUK MENINGKATKAN KEPUASAN KONSUMEN UMKM - Noornisa sarah Ginanjar; Sugih Prakoso (PT. ABIG RIZKY PUBLISHER, 2025)
This study aims to optimize product and service quality to improve customer satisfaction at the Sembako Kios Makmur UMKM located in Pelabuhan Ratu Market, Sukabumi Regency. Using a quantitative method with an associative approach, this study involved 96 respondents selected through probability sampling techniques. Data were collected using a questionnaire, then analyzed through prerequisite tests, multiple linear regression analysis, and hypothesis testing with the help of SPSS software. The results of the study indicate that product quality has a positive and significant effect on customer satisfaction. Likewise, service quality has been shown to have a positive and significant effect on customer satisfaction. Furthermore, product quality and service quality simultaneously have a significant effect on customer satisfaction. This finding underlines that the combination of good products and superior services is crucial in shaping customer satisfaction. The regression model built is able to explain 93.0% of the variation in customer satisfaction.